PHASEY BEAN (Macroptilium lathyroides (L.) Urb.) IS A POTENTIAL LOCAL LEGUM AS AN ANIMAL FEED - Suarna, I Wayan; Suryani, Ni Nyoman; Budiasa, I Ketut Mangku (Pastura, 2019)
Provision of animal feed in accordance with quality standards and adequate quantities has become a strategic need to increase livestock productivity and accelerate the availability and fulfillment of foodstuffs from livestock. In this regard, a survey research has been designed to study some of the local fodder plants that have superior potential as animal feed. Fodder plants are classified as superior feed varieties if they have properties: easy to breed, high productivity as a producer of forage and / or seeds, has a fast regrowth, is resistant to defoliation, resistant to grazing, resistant to environmental stresses, and palatable for livestock. Based on the results of the survey, several species of local animal feed plants that have superior characteristics have been found. One of them is a phasey bean plant (Macroptilium lathyroides (L.) Urb.). Phasey bean as a superior animal feed plant (TPT) besides being suitable for the above characteristics also has grown naturally in an area in Bali so it needs to be tested for its feasibility to be distributed throughout Bali. Keywords: phasey bean, superior legumes, tropical forage